Epidemiological evaluation of notified cases of tuberculosis in minas gerais, brazil - Tabai, Beatriz Joia; Pereira Bispo, Danilo (Brazilian Journal of Global Health, 2021)
OBJETIVO: Devido a situação de crescente pobreza em Minas Gerais e a gravidade da tuberculose, uma patologia associada a condições de instabilidade social, é necessário estudar a incidência de novos casos dessa doença para que medidas de saúde pública sejam tomadas a fim de reverter esse cenário. O objetivo deste estudo foi avaliar a incidência de casos notificados de tuberculose no estado de Minas Gerais entre 2015 e 2020. MÉTODOS: Esses dados foram coletados no Sistema de Notificações do Sistema Único de Saúde (DATASUS), via sistema TabNet. RESULTADOS: Entre 2015 e 2020, 24717 novos casos de tuberculose foram notificados em Minas Gerais, sendo 4053 em 2015, 4071 em 2016, 4055 em 2017, 4214 em 2018, 4349 em 2019 e 3975 em 2020. CONCLUSÃO: Assim, fica evidente que a prevenção e tratamento da tuberculose precisa de atenção. DESCRITORES: Tuberculose, Doenças Negligenciadas, Epidemiologia, Saúde Pública. ABSTRACT OBJECTIVE: Due to the situation of growing poverty in the state of Minas Gerais and the tuberculosis’ severity, a pathology associated with poor living conditions, it is necessary to study the incidence of new cases of this pathology so that public health measures can be taken to revert this scenario. So, the objective of this study is to evaluate the incidence of notified cases of tuberculosis in the state of Minas Gerais between 2015 and 2020. METHODS: The number of confirmed and notified cases of tuberculosis in the state of Minas Gerais from 2015 to 2020 was collected in the Information System of Notifiable Diseases of the IT department of the Brazilian Unified Health System (DATASUS), through the Tabnet system. Between 2015 and 2020, 24717 new cases of tuberculosis were reported in the Brazilian state of Minas Gerais. RESULTS: Regarding the year, 4053 occurred in 2015, 4071 in 2016, 4055 in 2017, 4214 in 2018, 4349 in 2019 and 3975 in 2020. CONCLUSION: For all of the foregoing, the great significance and need for attention focused on the prevention and treatment of Tuberculosis is highlighted. DESCRIPTORS: Tuberculosis, Neglected Diseases, Epidemiology, Public Health.